A numerical study on the wave loading on offshore structures of different cross-sectional geometries under the action of regular waves - Guilherme Fuhrmeister Vargas; Bruno Alvarez Scapin (The Journal of Engineering and Exact Sciences)
Coastal engineering and maritime hydraulics have experienced significant development over the years with the construction of bridges, oil exploration platforms, and ports, highlighting the importance of studying and quantifying the efforts resulting from wave loads on these structures. The present work aims to identify how a variation in the geometry of the cross-section, along the wave climate, can modify the magnitude of the wave loadings experienced by the structure. The open-source computational code OpenFOAM v. 4.1 was applied in the considered cases, along with the OlaFlow extension, considering the application of a structured mesh, the VOF (Volume of Fluid) methodology for representing the free surface, and the turbulence modeling according to Reynolds averaged equations (RANS). The results demonstrated that the shape of the cross-section plays an important role in the efforts experienced by the structure, and this influence is directly related to a characteristic length, whose intensification causes an increase in the magnitude of the experienced horizontal force. Likewise, by defining important dimensionless parameters, it was possible to obtain approximate expressions to determine the maximum wave force on the structures. The results and analyses carried out demonstrated that the force value calculated according to this approximation methodology is quite adequate, presenting relative errors smaller than 11,00%, corresponding to a relevant simplified approach for the determination of the maximum wave loads experienced by the structures, which can be important for proper design and analysis.